Literature Review: Environmental Awareness and Pro-Environmental Behavior - Wiwik Handayani; Reiga Ritomiea Ariescy; Felia Ananda Cahya; Salsabila Islami Yusnindi; Desy Ari Sulistyo (Future Science, 2020)
The purpose of this literature review is to review and explore the results of previous research and other literature related to environmental awareness and pro-environmental behavior. The research method used is a literature review. This study presents antecedents of Environmental awareness. Environmental awareness is very important to realize environmental protection behavior. The results of previous research indicate that environmental awareness has a significant role in building pro-environmental behavior. Someone will protect the environment if he realizes that the environment around him needs to be protected. Environmental awareness has a positive correlation with pro-environmental behavior. If someone has high environmental awareness, the pro-environmental behavior will also be higher.